Penerapan Asas Hakim Pasif terhadap Permohonan Dispensasi Perkawinan di Pengadilan Agama Soreang (International Forum of Researchers and Lecturers, 2025)
The Marriage Law regulates the minimum age limit for marriage is 19 (nineteen) years, but in practice underage marriages still often occur so that these marriages cannot be registered. Marriage dispensation becomes the legal legitimacy so that underage marriages can be registered in accordance with the provisions of Article 2 paragraph (2) of the Marriage Law. Marriage dispensation is obtained through the courts by involving the application of civil procedural law principles, including the principle of passive judges. This study aims to obtain an overview of the application of the passive judge principle and the limitations of active judges to the application for marriage dispensation at the Soreang Religious Court in relation to civil procedural law in the case of the application for underage marriage dispensation in Decision Number 421/Pdt.P/2023/PA.Sor. The research method and legal writing are carried out using a normative legal approach sourced from primary data and secondary data. Primary data is taken through interviews, then the secondary data used comes from literature studies. Based on the research results, it can be concluded that the application of the passive judge principle in marriage dispensation cases is dynamic and adjusted to the best interests of the child. The active role of the judge in providing advice and conducting in-depth examinations does not conflict with the passive judge principle, but is an effort to ensure a fair decision and protect the rights of the child.